Fabrication of bioinspired 3D-printed microtextures for efficient water harvesting using plasma treatment - Nithusha Kallingal (14149944) (2025)
Water harvesting from the air offers a promising solution to water scarcity in arid environments. A Namib Desert beetle is an inspiration for this purpose because of the unique combination of hydrophilic and hydrophobic areas on its wing scales to collect water; this study mimicked a similar system by creating hydrophilic patterns on a hydrophobic polymer substrate. Polydimethylsiloxane (PDMS) was chosen because of its hydrophobic character. The hydrophobicity of PDMS was improved through 3D micropatterning or modification by Silica (SiO2) nanoparticles to increase surface roughness. On the other hand, hydrophilicity is achieved by selective treatment of specific surface areas with low-temperature plasma. The fabricated microstructures were characterized using various analytical and imaging techniques to assess their morphology, chemical composition, and wettability. The water collection efficiency of the PDMS samples was tested using a humidifier as the water source, achieving a maximum rate of 1.14 ± 0.06 g/cm²h. Other Information Published in: Journal of Environmental Chemical Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jece.2025.115713